Long live the data! Embedded data management at a long‐term ecological research site. Issue 5 (13th May 2021) - Kaplan, Nicole E.; Baker, Karen S.; Karasti, Helena
Abstract: Open‐access data associated with research efforts depend upon managing, packaging, and preserving data for sharing with collaborators and the public. The U.S. Long‐Term Ecological Research (LTER) Network, established in 1980, provides an early example of embedded data management supporting long‐term, place‐based research and contributes to our understanding of the enactment of open data access within scientific research arenas. Here, we examine collective data activities enabled by embedding data management within the Shortgrass Steppe (SGS) research site. Study of the SGS LTER, a member of the U.S. LTER Network for more than three decades, provided a unique opportunity to investigate data management practices and challenges during the life cycle of a long‐term project. It illustrates how a continuous, uninterrupted focus on data management positioned in dynamic interaction with researchers at a site as well as with an active network‐wide data management committee can stimulate the growth of both data expertise and data infrastructure. We report on an ethnographic study by a collaborative team of researchers, all having been involved with the LTER network and well‐positioned for investigating data management challenges faced during the periods of activation, maturation, and decommissioning of a project at a research site. Termination of the SGS site's membership in the U.S. LTER Network prompted rethinking about long‐term data management. During the decommissioning phase, we document how views on temporality and data management strategies shift from planning for a longitudinal, ongoing site to wrapping up a long‐term project. Striving to ensure "long live the data" at the end, novel data arrangements, such as development of a digital legacy project collection, contribute to data stewardship. Lastly, from this study of a long‐term research site, we offer five recommendations about data management and describe strategies pertinent to planning for data management and open access for other research projects.